Debate on Public and Private Schools in Nepal - Koirala, Amit (International Journal of Social Sciences and Management, 2015)
There are various types of opinion on disparities between private and public school in Nepal lead a debate on whether school education should privatize or not. There are opinions in for and against the privatization in school education. Some people argue that the privatization in school education should not be promoted. It creates two classes citizens. Similarly some people argue that the school education is entirely responsible of the government. On the other hand, some gives logic that the government is failure to offer quality education to all children due shortage of funds so, this paper tries to explore the existing debate on public and private schools in Nepal. DOI: http://dx.doi.org/10.3126/ijssm.v2i1.11882 Int. J. Soc. Sci. Manage. Vol-2, issue-1: 3-8